Relation of Abnormal Cytological Smears and Carcinoma of Cervix Uteri to Husband's Occupation. Issue 5859 (21st April 1973) - Wakefield, John; Yule, R.; Smith, Alwyn; Adelstein, A. M.
Abstract : An analysis of the cytological records of almost 300, 000 women in the Manchester area shows that the rates of positive/suspicious findings from population screening are highly correlated with the rates of mortality from cancer of the cervix when both are distributed according to the occupation of the husband. The correlation holds for various occupational groupings and for all the individual occupation units in which there are more than 1, 000 women. This evidence strengthens the case for believing that the condition revealed by a positive smear is a stage in the development of invasive cancer of the uterine cervix.